DOMINASI KARAENG DALAM PILKADA DI JENEPONTO - Haboddin, Muhtar (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Islam 45, 2023)
This article explains the dominance of karaeng in the regional elections in the Jeneponto district. Karaeng is part of the traditional elite who can seize and maintain power through regional elections which are carried out directly, freely, fairly, and democratically. The karaeng's victory in the 2018 regional elections proves that in the last twenty years, the karaeng's position as a governing elite has become stronger. This means that the nobility in Jeneponto has a stronger position in the direct struggle for power. The 2018 regional elections proved that all regional head candidate pairs had Karaeng backgrounds. By mastering this candidacy, the karaeng will automatically be elected and become the regional head